Opportunities for organocatalysis in polymer synthesis via step-growth methods. (March 2019) - Bossion, Amaury; Heifferon, Katherine V.; Meabe, Leire; Zivic, Nicolas; Taton, Daniel; Hedrick, James L.; Long, Timothy E.; Sardon, Haritz
Graphical abstract: Abstract: Organocatalysis has emerged as an invaluable tool for polymer synthesis and has already demonstrated versatility for replacing organometallic catalysts in many polymerization reactions. The overall ease of removal and lower toxicity of organocatalysts relative to their common metal counterparts has also nurtured development especially in chain growth polymerizations to achieve precision macromolecular architectures for application in the biomedical space. The application of organocatalysts in step-growth polymerizations of polymers, including polyesters, polycarbonates, and polyurethanes, has garnered fewer studies in spite of the large array of benefits that could be achieved. Step-growth polymers account for nearly 20 wt. % of the Word Plastic Production and play a vital role in many technologies as engineering plastics and high performance polymeric materials with outstanding thermomechanical performance. Step-growth polymerizations are achieved using monomers with a diversity of chemical functionality. Consequently, a vast array of polymeric structures are attainable and will impact diverse applications in energy, aerospace, medicine, transportation, and construction. This review article will highlight the recent advances in organocatalysis in step growth polymerizations. We will primarily focus our review on the synthesis of commercially important polyesters and polyurethanes using organocatalysis, however, the review will also emphasize recent literature describing less explored polymers, such as polyethers, polycarbonates, and polybenzoins, which have recently employed organocatalysts. Moreover, the article will draw attention to recent efforts in the use of carbon dioxide as a monomer for the preparation of step-growth polymers in the presence of organocatalysis.